The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1126/scitranslmed.aai7786
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of rifapentine and rifampin in a rabbit model of tuberculosis and correlation with clinical trial data

Abstract: In clinical trials of two rifamycin antibiotics (rifampin and rifapentine) for treating tuberculosis (TB), patients with cavitary lung lesions did not appear to derive benefit from rifapentine. Rifapentine was found not to outperform rifampin, despite a lower minimum inhibitory concentration against in mouse models of TB. To understand these findings, we have developed a rabbit model of TB that reliably develops lung cavities with features similar to those of patients with pulmonary cavitary TB. After single o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“… 41 43 In addition, the rabbit is the elected model for pharmacokinetic studies due its strong correlation with clinical trials. 44 For instance, the rabbit ear scar model was successfully used prior to a Phase I randomized clinical trial for safety and tolerability of topically delivered kynurenic acid in humans and randomized controlled trials. 45 Thus, the rASC fast proliferation consists of an advantageous characteristic, promoting vast MSC availability for both in vitro and in vivo applications with a great translation described to human clinical medicine.…”
Section: Discussionmentioning
confidence: 99%
“… 41 43 In addition, the rabbit is the elected model for pharmacokinetic studies due its strong correlation with clinical trials. 44 For instance, the rabbit ear scar model was successfully used prior to a Phase I randomized clinical trial for safety and tolerability of topically delivered kynurenic acid in humans and randomized controlled trials. 45 Thus, the rASC fast proliferation consists of an advantageous characteristic, promoting vast MSC availability for both in vitro and in vivo applications with a great translation described to human clinical medicine.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was further supported by studies demonstrating that clofazimine diffuses relatively poorly into caseous necrotic lesions in humans TB (27), does not have bactericidal activity in ex vivo caseum from M. tuberculosis -infected rabbits (41), and the long-standing observation that clofazimine accumulates in macrophages (26, 27, 42, 43). Rifapentine has been shown to diffuse into necrotic caseous lesions less rapidly than rifampin in a rabbit model of cavitary TB (28), a finding that correlates with clinical data indicating that replacing rifampin with rifapentine added proportionally less activity in patients with cavitary versus non-cavitary TB disease (44). It has also been reported that rifapentine accumulates in macrophages and is relatively more active against intracellular than extracellular M. tuberculosis (25).…”
Section: Discussionmentioning
confidence: 68%
“…weeks. Because the lungs of TB patients feature a heterogeneous array of lesion types resulting in diverse microenvironments and pharmacological compartments that alter the drug susceptibility and drug exposure of resident tubercle bacilli (25,26), we used both C3HeB/FeJ mice, which develop caseating lung lesions in response to infection, and BALB/c mice, which do not, to investigate the impact of host pathology on mutant selection. Despite lower CFU counts on the day after infection (W-8) in C3HeB/FeJ mice (1.67 log 10 CFU per lung) compared to BALB/c (2.26 log 10 ) (p <0.001), higher CFU counts were observed in C3HeB/FeJ mice 8 weeks later, on the day treatment started (D0), and after 3 weeks of treatment in almost all groups (p <0.001 -0.05) ( Fig.…”
Section: Spontaneous Pretomanid-resistant Mutants Exist At a Relativementioning
confidence: 99%